Silvi-pastoral system for ensuring fodder availability and site improvement: Astudy under arid conditions in Bhuj, Kachchh - Arya, Ranjana; Kumar, Hemant; Lohara, R.R.; Meena, R.L. (Indian Journal of Agroforestry, 2020)
Silvi-pastoral systems are of paramount importance in livestock based economies as these systems have higher biomass output per unit land area over the productivity of single component based land use systems. A siIvipastoral field trial was conducted on shallow degraded hilly pediment soil at Mochirai, Bhuj in 2006 with four tree species namely C. gharaf, P cineraria, Z. mauritiana C. mopane and C. ciliaris as grass. Grass was sown manually using low seed rate in 1.0 m strip at a distance of 4 m. Findings revealed that integration of grass with trees enhanced survival of trees (97.5%) at 64 months as compared to control (87.6%). Trees planted with grass recorded 10.7% more mean green biomass (6.96 kg tree-1) as compared to control (6.29 kg tree-1), Difference was more pronounced in case of Z. mauritiana. Species wise green biomass yield was 5.3 to 4.5 kg treefor z. mauritiana and 8.6 to 8.0 kg treefor C. gharaffor with grass and control treatments, respectively. The green grass yield vary from 0.67 to 1.94 kg/m2 in different years. The overall data analysis of grass yield for five years indicated that annual grass yield variation and effect of tree species was highly significant at p-O.OO. The total green biomass yield was maximum in C.gharaf: C. ciliaris (6137.8 kg ha-1) silvipastoral systems followed by Z. mauritiana: C. ciliaris (4512.7 kg ha-1). Same trend was obtained for dry biomass yield. Thus, it can be concluded that grass sowing in small strips along the trees promoted the plant growth.